An Improved ICI Self Cancellation Scheme for OFDM Systems Under Various Channels - A. H. Sharief; M. Satya Sai Ram (Institute of Advanced Engineering and Science, 2016)
Inter Carrier Interference (ICI) is being introduced in OFDM due to the carrier frequency offset (CFO), which will degrade the system performance and efficiency at higher modulation levels and it decreases the performance of power amplifiers. Hence, here in this paper, we introduced a novel ICI reduction algorithms cancellation under the various channel environments such as AWGN, Rayleigh and also Rician. Simulation results have been compared with existing and proposed schemes under these channel specifications and concluded that the Rayleigh has performed far better than the AWGN and Rician channel distributions in terms of Bit Error Rate (BER) and Carrier interference Ration (CIR) performance.